Teachers' perception and willingness towards educational video games: case of young Moroccan physics teachers - Khouna, Jalal; Achour, Mohamed; Echantoufi, Noureddine; Hamzi, Amine; Tahiri, Ahmed (Journal of Education and Learning (EduLearn), 2025)
Recent studies have shown that teachers ‘perception and attitudes about digital tools play a crucial role in how they integrate and use technology in the classroom. The purpose of the present study is to investigate physics teachers’ perception and willingness towards educational video games (EVGs). Based on the literature review, a questionnaire was developed and employed in data collection, and statistic results were generated for data analysis. A sample consisting of 91 teachers participated in this survey. The result shows that the majority of teachers know about the use of EVGs in teaching physics and expect that the use of this tool in the classroom will have an added value to learners, especially in terms of motivation, simulating physical phenomena, and comprehending concepts. Moreover, more than three-quarters of the young teachers, who polled, reported an interest in using EVGs and a willingness to receive training in this area. Finally, we conclude with some recommendations about future use of EVGs in teaching physics.